Wood resistance of Gmelina arborea on the attack by white-rot fungi of Trametes versicolor treated with clove leaves extract. - Ira Taskirawati; Fadhli Dzil Ikram; Musrizal Muin (Kementerian Perindustrian, 2022)
Wood with low durability class or low natural durability has low resistance to attack by wood-destroying organisms, so it is very susceptible to attack by wood destroying organisms such as wood rot fungi. This study aims to determine the resistance of Gmelina arborea wood from clove leaf extract treatment to white-rot fungus attack. The cold soak method was used to apply clove leaf extract to wood samples and exposed to Trametes versicolor for three months. Analysis of retention data used a split-plot design with four levels of treatment, namely concentrations of 15%, 20%, 25%, and control. Each treatment was repeated three times. The SNI 01-7207-2014 wood resistance class table determines the wood resistance class. The results showed an increase in the retention value of gmelina wood in line with the increase in the given concentration. Therefore, testing the resistance of gmelina wood to fungal attack, treated with clove leaf extract on the heartwood with a concentration of 20% and 25%, could increase the wood resistance from moderately resistant to resistant. As well as, giving 25% concentration in the sapwood can increase the wood resistance from moderately resistant to resistant.